SENSITIZING POTENTIAL OF TEMPORARY FILLING MATERIALS - Miglena Balcheva; Boris Valkov (Peytchinski Publishing, 2024)
Introduction: When treatment requires multiple visits, temporary filling materials are needed in order to seal the cavity between the appointments. Some of their substances can be contact allergens. Although the risk is very low, it should not be ignored. The aim of the study is to establish the sensitizing potential of temporary filling materials. Materials and methods: In order to confirm allergy to temporary filling materials, we used a patch test with a panel of 9 allergens - components of temporary filling materials with established strong sensitizing properties. Results: The results showed that sensitization and polysensitization to the examined dental materials are registered more often in women than men and zinc (Zn) is the most common sensitizer among the ingredients of temporary filling materials. Cross-sensitization between acrylates is also found. Conclusion: There is an extremely small risk for the ingredients of the temporary filling materials to cause oral symptoms.